2020
DOI: 10.1088/1757-899x/778/1/012071
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study on the pyrolysis of low-density polyethylene (LDPE) waste using kaolin as catalyst

Abstract: The increase in the industrial and urban activities has resulted in the rise of plastic production and consumption. The higher demand for plastic causes accumulation of plastic waste in which it contributes to environmental problems. About 65-70% of plastic waste is a type of Low-Density Polyethylene (LDPE). To reduce this type of waste, the pyrolysis method can be an alternative. This study investigated the catalyst ratio and particle size of the material. The results indicate that the optimum catalyst was at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This temperature range was used in order to separate fractions that could possibly include aviation kerosene, which could possibly be part of the pyrolyzed oil. The factors were chosen according to the works developed in the literature (Erawati et al 2020). Through CG-MS Agilent 7820 column C18 it was possible to identify the closest proximity of the oil by comparing the peak areas with diesel, gasoline and aviation kerosene standards.…”
Section: Methodsmentioning
confidence: 99%
“…This temperature range was used in order to separate fractions that could possibly include aviation kerosene, which could possibly be part of the pyrolyzed oil. The factors were chosen according to the works developed in the literature (Erawati et al 2020). Through CG-MS Agilent 7820 column C18 it was possible to identify the closest proximity of the oil by comparing the peak areas with diesel, gasoline and aviation kerosene standards.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the yield of aromatic hydrocarbons increases with the reuse of the catalyst, which is associated with an increase in particle size [ 16 ]. The optimal size of kaolin particles was investigated in the work of Erawati et al, where it was established as 7.5 × 6.5 cm [ 19 ].…”
Section: Kaolin Group Catalytic Activitymentioning
confidence: 99%
“…In summarizing, the highest liquid yields described in the articles concerned with kaolin catalysts for different plastics are 78.7 wt% for HDPE over nitric acid-treated kaolin [ 14 ], 99.82 wt% for LDPE on neat kaolin powder [ 19 ], 92 wt% for PP on sulfuric acid-treated kaolin [ 25 ], and 96.37 wt% for PS over pristine kaolin [ 29 ]. Quite expectably, the most efficient catalysts were obtained using acidic treatment, which led to the generation of a sufficient number of acidic sites.…”
Section: Kaolin Group Catalytic Activitymentioning
confidence: 99%